2007
DOI: 10.1007/s11663-007-9042-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Liquid Flow in a Packed Bed in the Presence of Gas Flow

Abstract: Liquid metal and slag descend through a porous coke matrix in the lower part of an iron making blast furnace. The size of the raceway is an important factor in determining the gas penetration into the bed, which pushes the liquid toward the deadman region. This, in turn, affects the gas flow in the bed. The current study tries to explain theoretically the effect of cavity size hysteresis on gas-liquid distribution in a packed bed. The liquid flow has been modeled considering it to be discrete in nature. The tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Knowing the correct shape and size of the cavity helps in understanding the heat, mass and momentum transfer accurately in these reactors. 1,2) Using the proper theory [3][4][5] or correlations, [6][7][8][9][10] it is possible to predict the raceway size in a reasonable way for both increasing and decreasing gas velocity case. However, hardly any theory, using continuum approach, is available to predict the raceway shape which also affects the aerodynamics of the blast furnace and thus the heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the correct shape and size of the cavity helps in understanding the heat, mass and momentum transfer accurately in these reactors. 1,2) Using the proper theory [3][4][5] or correlations, [6][7][8][9][10] it is possible to predict the raceway size in a reasonable way for both increasing and decreasing gas velocity case. However, hardly any theory, using continuum approach, is available to predict the raceway shape which also affects the aerodynamics of the blast furnace and thus the heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The point at which the liquid detaches from the upper particle and falls on the lower particle is governed by the moment equation. 26) As long as moment of the liquid (about the detachment point) moving on the particle is less than zero, the liquid stays in contact with the particle; otherwise, it detaches and falls on the lower particle.…”
Section: Modeling Of Liquid Flowmentioning
confidence: 99%
“…An X-ray technique is used to visualize the liquid flow. 25,26) Their study revealed that liquid percolates as a series of droplets and rivulets in a non-wetting system. So, the modelling of nonwetting liquid flow via the continuum hypothesis would be in serious contradiction to the observation when the system is non-wetting or when the liquid flow rate is low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, Singh et al has come up with a model, where they have taken care of the phenomena of droplet detaching from the solid surface by moment balance equation and rupture of rivulet phenomena. When the moment becomes negative, it has been assumed that liquid detaches from the solid surface.…”
Section: Liquid Flowmentioning
confidence: 99%